2003
DOI: 10.1001/archinte.163.3.347
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Chronic Heart Failure

Abstract: The adaptation of state-of-the-art computerized technology to closely monitor patients with HF with advanced-practice nurse care under the guidance of a cardiologist significantly improves HF management while reducing the cost of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
216
2
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(233 citation statements)
references
References 25 publications
10
216
2
5
Order By: Relevance
“…The cost savings were attributed to fewer hospitalizations while the quality of care remained stable. Benatar et al 6 and Dansky et al 2 both significantly decreased hospitalization charges for their randomized telehomecare patients versus controls.…”
Section: Effects On Costsmentioning
confidence: 93%
See 3 more Smart Citations
“…The cost savings were attributed to fewer hospitalizations while the quality of care remained stable. Benatar et al 6 and Dansky et al 2 both significantly decreased hospitalization charges for their randomized telehomecare patients versus controls.…”
Section: Effects On Costsmentioning
confidence: 93%
“…Research has shown decreased rehospitalization rates in patients with HF, 4,6,7,28 diabetes, 2,21 and spinal cord injury 8 ; better diabetic management 16 ; and the ability to assess chronic wound progression using telecommunications technology. 9 However, variations in sample characteristics, such as age, equipment type used, intervention length, and study design, make generalizations difficult.…”
Section: Effects On Chronic Illnessmentioning
confidence: 99%
See 2 more Smart Citations
“…In diabetes, several studies demonstrated reduced glycosylated hemoglobin levels after use of telemedicine systems [5][6][7][8][9][10] . In congestive heart failure, telemedicine improved quality of life, decreased hospitalizations, and decreased hospitalization costs in the telemedicine group [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%